The Effects of Productivity and Liquidity on the Profitability of Islamic Banks in Indonesia - Muhamad Nadratuzzaman Hosen; Syafaat Muhari; Kevin Costner Kardius (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. This study is to measure and analyze the levels of productivity and liquidity of Islamic Banks in Indonesia. This study uses a non-parametric method, contrived from the Malmquist Productivity Index, to measure and analyze the level of productivity of Islamic Banks. Also, this study uses the Liquidity Creation (LC) scale as a liquidity indicator. The regression of the Tobit model is used to measure the effects of independent variables, namely; productivity, liquidity, Financing to Deposit Ratios/FDR, Non-Performance Financing/NPF, and the Capital Adequacy Ratio/CAR, on the profitability of Islamic banks, as represented by Return on Assets/ROA. This study shows that FDR, NPF, and CAR are statistically significant to ROA, while Total Factor Productivity/TFP and LC are not statistically significant. Other results show the level of productivity of Islamic Banks decreased during the period 2011-2020. In terms of liquidity level, Islamic banks did have a sound level of liquidity, based on mapping the criteria of FDR, NPF, and CAR, where the LC always grew. This study shows the novelty of integrating productivity, liquidity, and profitability techniques, to measure Islamic Banking Performance in Indonesia.Keywords: Islamic Bank, Total Factor Productivity, Liquidity Creation, ProfitabilityJEL: G21, R51 Abstrak. Tujuan dari penelitian ini adalah untuk mengukur dan menganalisis tingkat produktivitas dan likuiditas Bank Umum Syariah di Indonesia. Penelitian ini menggunakan metode non parametrik yakni Malmquist Productivity Index untuk mengukur dan menganalisis tingkat produktivitas Bank Umum Syariah. Selain itu, penelitian ini menggunakan Liquidity Creation (LC) sebagai indikator likuiditas. Regresi model Tobit digunakan untuk mengukur pengaruh variabel bebas, yaitu; produktivitas, likuiditas, Financing to Deposit Ratio/FDR, Non-Performance Financing/NPF, dan Capital Adequacy Ratio/CAR terhadap profitabilitas bank syariah yang direpresentasikan oleh Return on Assets/ROA. Penelitian ini menunjukkan bahwa FDR, NPF, dan CAR berpengaruh signifikan terhadap ROA, sedangkan Total Factor Productivity/TFP dan LC tidak berpengaruh signifikan. Hasil lainnya menunjukkan bahwa tingkat produktivitas Bank Umum Syariah menurun selama periode 2011-2020. Dari sisi tingkat likuiditas, bank syariah memang memiliki tingkat likuiditas yang sehat berdasarkan pemetaan kriteria FDR, NPF dan CAR, dimana LC selalu meningkat setiap periode. Studi ini menunjukkan kebaruan dalam integrasi teknik produktivitas, likuiditas, dan profitabilitas, untuk mengukur kinerja perbankan Syariah di Indonesia. Keywords: Bank Syariah, Total Factor Productivity, Liquidity Creation, ProfitabilityJEL: G21, R51